Recognising the dynamics that surround drought impacts. (October 2018) - Few, Roger; Tebboth, Mark G.L.
Highlights: Multiple environmental and societal dynamics shape drought risk. Interacting dynamics accentuate challenges for drought response in drylands. Effective reduction of drought risk can seldom be achieved as a standalone measure. A more integrated approach can bring co-benefits and enhance sustainability.